Enrichment and Detection of Antigen-Binding B Cells for Mass Cytometry - Zachary C. Stensland; Mia J. Smith (Magnetochemistry, 2021)
Over the years, various techniques have been utilized to study the function and phenotype of antigen-binding B cells in the primary repertoire following immunization, infection, and development of autoimmunity. Due to the low frequency of antigen-reactive B cells (<0.05% of lymphocytes) in the periphery, preliminary enrichment of cells is necessary to achieve sufficient numbers for statistically sound characterization, especially when downstream analytic platform use, e.g., CyTOF, is low throughput. We previously described a method to detect and enrich antigen-reactive B cells from peripheral blood and tissues using biotinylated antigens in conjunction with magnetic nanoparticles, preparative to a downstream analysis by ELISPOT and flow cytometry. While mass cytometry (CyTOF) enables high dimensional immunophenotyping of over 40 unique parameters on a single-cell level, its low throughput compared to flow cytometry and requirement for removal of metal contaminants, such as nanoparticles, made it particularly unsuitable for studies of rare cells in a mixed population. Here we describe a novel CyTOF-compatible approach for multiplexed enrichment of antigen-reactive B cells, e.g., insulin and tetanus toxoid, using cleavable magnetic nanoparticles. This method allows improved monitoring of the phenotype and function of antigen-reactive B cells during the development of disease or after immunization while minimizing the amount of sample and run times needed.